Improvement on corrosion and wear resistance of graphene-based coatings: A review - Thivagaran, Rihashni; Mohd Radzi, Aridi; Nurjannah, Salim; Chong, Kwok Feng; Nurul Huda, Abu Bakar (Trans Tech Publications, Switzerland, 2024)
Poor corrosion and wear resistance of metallic materials lead to deterioration of their properties and may cause failures. In fundamental, corrosion is due to the reaction of metals with their surroundings, such as moisture, salts, and air pollutants. On the other hand, wear is a surface failure because of continuous dynamic contact between the metals' surfaces and other surfaces. In this regard, surface protection such as coatings is crucial to ensure the long life of the metallic materials. Among the surface protection available, graphene-based coatings have emerged as the most researched topic due to their excellent impermeability, chemical inertness, high hardness, and flexibility. It is reported that graphene-metal and graphene-polymer nanocomposite coatings offer versatile protection against corrosion and abrasive wear. Therefore, this review presents the current state-of-the-art graphene-based nanocomposite coatings in the field of corrosion and abrasive wear resistance. This review provides significant approach of graphene-metal and graphene-polymer, as well as the future perspectives of graphene-based coatings.